Penerapan Implementasi Kurikulum Merdeka - Rosmawaty Rosmawaty; Salwa Zulma Balqis; Qorima Melati; Alika Putri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe various obstacles in the implementation of the Merdeka Curriculum in Indonesian language learning. The method used in this research is descriptive qualitative with data collection techniques in the form of a literature review. Data were obtained from various sources such as scientific journals, books, and official documents relevant to the research topic. The data analysis technique was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that there are several main obstacles in the implementation of the Merdeka Curriculum, namely teachers' difficulties in understanding and developing the Learning Outcomes (Capaian Pembelajaran/CP) and the Learning Objective Flow (Alur Tujuan Pembelajaran/ATP), limitations in applying innovative learning models, lack of supporting facilities and infrastructure, and low student readiness to participate in student-centered learning. Furthermore, limited training and mentoring for teachers also act as inhibiting factors. Therefore, efforts are needed to improve teacher competencies, provide adequate facilities, and ensure continuous policy support so that the implementation of the Merdeka Curriculum can run optimally in Indonesian language learning.